Testing the correlation between the vertical crustal movements and temperature changes on the example of selected vectors permanent GNSS stations - Kowalczyk, Kamil (International Conference “Environmental Engineering”, 2017)
In the last years air temperature increasing gradual. It also changes depending on the area: metropolitan, rural. The temperature changes directly affects the expansion of materials of which are made geodetic control network and support infrastructure. This may be influenced on the daily change in the amount determined for permanent GNSS stations. The main aim of the article is to examine the relationship between height changes and temperature changes. Daily difference in height between the selected stations Polish ASG EUPOS and the temperature in the vicinity of the stabilization of these stations data were used. Three year period was taken to the analysis. The results give a view on the article thesis.
Keywords: temperature; vertical crustal movements; testing correlation